Heterologous Expression of the Pyrenophora tritici-repentis Effector Proteins ToxA and ToxB, and the Prevalence of Effector Sensitivity in Australian Cereal Crops - Moffat, Caroline; See, Pao Theen; Iagallo, Elyce M; Oliver, Richard P (FRONTIERS MEDIA SA, 2019)
Here, we evaluate the expression of the proteinaceous effectors ToxA and ToxB, produced by the necrotrophic fungal pathogen Pyrenophora tritici-repentis, which confer tan spot disease susceptibility on wheat. These necrotrophic effectors were expressed in two heterologous systems: Escherichia coli and Pichia pastoris. The E. coli SHuﬄe system was demonstrated to be superior to P. pastoris in generating high-levels of recombinant proteins that were soluble and stable. In addition, protein extracts from P. pastoris induced non-specific chlorosis on wheat, postulated to be caused by co-purified glucanases secreted by the host. Up to 79.6 μg/ml of ToxB was obtained using the SHuﬄe system in the absence of the native signal peptide, whilst the ToxA yield was considerably lower at 3.2 μg/ml. Results indicated that a histidine tag at the ToxA C-terminus interfered with effector functionality. Heterologously expressed ToxA and ToxB were tested on a panel of Australian cereals, including 122 varieties of bread wheat, 16 durum, 20 triticale and 5 barley varieties, as well as common plant model species including tobacco and Arabidopsis thaliana. A varying degree of effector sensitivities was observed, with a higher ToxB sensitivity and prevalence in the durum and triticale varieties. ToxB-induced chlorosis was also detected on barley. The heterologous expression of effectors that are easily scalable, will facilitate effector-assisted selection of varieties in wheat breeding programs as well as the investigation of P. tritici-repentis effectors in host and non-host interactions.